Pemikiran Etika Pasar Imam Ghazali - Suprihatin . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
There is a market perception that ethics is not part of the discussion of religion. This is evidenced by the development of a market ethic rooted in materialism as Capitalism and Socialism. However, Imam Ghazali thought it can he seen that the ethical teachings of religfon also contained market which can encourage physical and spiritual welfare of human beings. This study uses the contents of the corroboration approach (comparing the two states) and "koligasi" (interpreting the special circumstances associated with the common conception). This research resulted in the concept of ethical behavior in the marketplace that can be operationalized in the cognitive, affective andpsychomotor